Reconfiguring Tax Sovereignty under the OECD Two-Pillar Framework: Legal and Institutional Readiness in a Developing Economy - Heriantonius Silalahi (Inovasi Analisis Data, 2025)
Purpose – This article looks at how developing countries deal with the OECD's two-pillar international tax framework while protecting their own taxing abilities. Design/methodology/approach – A qualitative, normative, juridical, and comparative policy-analytical method guides the study. Domestic tax laws, international tax treaties, and institutional arrangements are examined through doctrinal and comparative legal analysis to determine the country's preparedness for implementing the new global tax architecture. Findings – The findings show that readiness for the two-pillar framework is not black and white, or homogeneous, but rather incremental. The pace of legal transplants and administrative capacity development varies; sovereign concerns strongly influence the sequence of reform. Rather than being a form of opposition to global coordination, partial alignment seems to be a deliberate tactic for negotiating the institutional constraints and distributive risks that are part and parcel of the process of harmonising international taxes. Originality/value – The paper contributes to the concept of adaptive fiscal sovereignty, showing that readiness for global tax reform is emergent rather than being solely an end-point in compliance. The text is among the first to take a thorough look at the connection between legal preparedness, administrative capacity and sovereign jurisdiction in the OECD's two-pillar approach. Research Implications – The results expand the existing literature on international tax governance by offering a new interpretation of readiness for implementation as a tactical policy option. Academic researchers and policymakers interested in fair processes for incorporating international tax norms within developing countries can find valuable insights here.